To add 4(g-2)+(g+2), we can distribute the 4 to both terms inside the parentheses:
4(g-2) = 4g - 8
So the expression becomes:
4g - 8 + (g + 2)
Now, we can combine like terms by adding the terms with the same variable:
4g + g = 5g
And -8 + 2 = -6
Therefore, the final expression is:
5g - 6
Use the properties of operations to add 4(g−2)+(g+2)
4
(
−
2
)
+
(
+
2
)
.(1 point)
7 answers
Use the properties of operations to subtract (h+k)−(2k−h)
(
ℎ
+
)
−
(
2
−
ℎ
)
.(1 point)
(
ℎ
+
)
−
(
2
−
ℎ
)
.(1 point)
To subtract (h+k) - (2k-h), we can distribute the negative sign to both terms inside the second parentheses:
(h + k) - (2k - h) = h + k - 2k + h
We can now combine like terms:
(h + h) + (k - 2k) = 2h - k
Therefore, the final expression is:
2h - k
(h + k) - (2k - h) = h + k - 2k + h
We can now combine like terms:
(h + h) + (k - 2k) = 2h - k
Therefore, the final expression is:
2h - k
Use the properties of operations to subtract (p−3)−(2.4+2p)
.(1 point)
.(1 point)
To subtract (p-3) - (2.4 + 2p), we can distribute the negative sign to both terms inside the second parentheses:
(p - 3) - (2.4 + 2p) = p - 3 - 2.4 - 2p
Now, let's simplify the expression by combining like terms:
(p - 2p) + (-3 - 2.4) = -p - 5.4
Therefore, the final expression is:
-p - 5.4
(p - 3) - (2.4 + 2p) = p - 3 - 2.4 - 2p
Now, let's simplify the expression by combining like terms:
(p - 2p) + (-3 - 2.4) = -p - 5.4
Therefore, the final expression is:
-p - 5.4
Subtract: 2(k−4)−3(2k−1)
2
(
−
4
)
−
3
(
2
−
1
)
.(1 point
2
(
−
4
)
−
3
(
2
−
1
)
.(1 point
To subtract 2(k-4) - 3(2k-1), we can first distribute the coefficients:
2(k-4) = 2k - 8
3(2k-1) = 6k - 3
Now, we can subtract the two expressions:
(2k - 8) - (6k - 3) = 2k - 8 - 6k + 3
Combine like terms:
(2k - 6k) + (-8 + 3) = -4k - 5
Therefore, the final expression is:
-4k - 5
2(k-4) = 2k - 8
3(2k-1) = 6k - 3
Now, we can subtract the two expressions:
(2k - 8) - (6k - 3) = 2k - 8 - 6k + 3
Combine like terms:
(2k - 6k) + (-8 + 3) = -4k - 5
Therefore, the final expression is:
-4k - 5